That compassionate touch of Ma Anandamayee - Chaudhuri, Narayan, 1912- (Motilal Banarsidass, 1980)
Hagiography of Hindu woman religious leader Ānandamaẏī (popularly known as Ma Anandamayee), b. 1896; includes selected discourses.